2022
DOI: 10.3389/fonc.2021.824204
|View full text |Cite
|
Sign up to set email alerts
|

TRUS-Guided Target Biopsy for a PI-RADS 3–5 Index Lesion to Reduce Gleason Score Underestimation: A Propensity Score Matching Analysis

Abstract: BackgroundMagnetic resonance imaging (MRI) and transrectal ultrasound (TRUS)-guided cognitive or image fusion biopsy is performed to target a prostate imaging reporting and data system (PI-RADS) 3–5 lesion. Biopsy Gleason score (GS) is frequently underestimated compared to prostatectomy GS. However, it is still unclear about how many cores on target are necessary to reduce undergrading and if additional cores around the target may improve grade prediction on surgical specimen.PurposeTo determine the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In the present study, to improve the CDR and Gleason score underestimation, a targeted biopsy with a large number of cores (approximately six cores), including index lesion peripheral biopsy, was performed to compensate for the weakness of cognitive biopsy. 18 In our previous study, we reported that a target biopsy of five cores or more, including the center of index lesion and peripheral tissues, can expect optimal CDR and avoid Gleason score underestimation. 18 In the present study, a mean of 5.96 core biopsy were performed on the index lesions.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In the present study, to improve the CDR and Gleason score underestimation, a targeted biopsy with a large number of cores (approximately six cores), including index lesion peripheral biopsy, was performed to compensate for the weakness of cognitive biopsy. 18 In our previous study, we reported that a target biopsy of five cores or more, including the center of index lesion and peripheral tissues, can expect optimal CDR and avoid Gleason score underestimation. 18 In the present study, a mean of 5.96 core biopsy were performed on the index lesions.…”
Section: Discussionmentioning
confidence: 92%
“… 18 In our previous study, we reported that a target biopsy of five cores or more, including the center of index lesion and peripheral tissues, can expect optimal CDR and avoid Gleason score underestimation. 18 In the present study, a mean of 5.96 core biopsy were performed on the index lesions.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several recent studies indicate that SB may reduce the likelihood of Gleason score underestimation [36,37]. Moreover, taking cores from areas surrounding a suspicious lesion (focal systematic biopsy) can overlap sampling error and may provide a better estimation of the Gleason score [38]. Similarly, several technical issues of TB are also under investigation.…”
Section: Discussionmentioning
confidence: 99%